Market Entry Strategy of EF Education First - Zadražilová, Lucie; Král, Petr, 1979-; Peterková, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
The principal goal of its thesis is to conduct a research and do the analyses necessary for the decision whether to enter a foreign market and in case of positive answer the entry strategy is to be suggested. The research and analyses are done on the case of EF Education First, a global company doing its business activities in the educational sector with the main specialization in language learning, and the market of Ukraine. The thesis is divided into a theoretical part which summarizes main elements and academic knowledge important for the entry market strategy including modes of entry, international specifics, marketing of services and 7Ps. In the practical part, the findings from the PEST analysis conducted on the Ukrainian market are presented and the internal environment of the company is analyzed. The two main strategies are selected and their advantages and potential limitations are presented. The final recommendation is made.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses